Typh fevers: a combination of Typhoid and Typhus - Manappallil, Robin George (Asian Journal of Medical Sciences, 2017)
Typhoid fever is caused by Salmonella typhi, while typhus fever is a rickettsial infection. In both cases the patients present with almost similar pattern of illness and are often misdiagnosed. This is the case of a young lady who presented with 10 days history of fever and was diagnosed to have typhoid fever. She continued to be febrile despite ceftriaxone therapy. She was later found to have a typhus coinfection and improved with addition of doxycycline. Asian Journal of Medical Sciences Vol.8(6) 2017 40-41